2003
DOI: 10.1017/s0012162203001415
|View full text |Cite
|
Sign up to set email alerts
|

Clinical utility of the Duncan-Ely test for rectus femoris dysfunction during the swing phase of gait

Abstract: The Ely Test (or Duncan-Ely test) has been accepted as a clinical tool to assess rectus femoris spasticity by passively flexing the knee rapidly while the patient lies prone in a relaxed state. In this retrospective review, patients' dynamic knee range of motion (ROM) during gait and an electromyogram (EMG) were compared with the results of the Ely test. Data for 70 patients (44 males, 26 females; 104 limbs) were included. Mean age of patients was 13 years, SD 9 years, range 4 years 5 months to 54 years. All p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
28
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 8 publications
0
28
0
Order By: Relevance
“…Indications for RFT are a positive Duncan‐Ely test and diminution of at least 15° of the total range of knee flexion during the swing phase . A study revealed that the Duncan‐Ely test had a good positive predictive value for rectus femoris dysfunction during gait . Therefore, a positive result in the Duncan‐Ely test might be a surgical indication for RFT.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Indications for RFT are a positive Duncan‐Ely test and diminution of at least 15° of the total range of knee flexion during the swing phase . A study revealed that the Duncan‐Ely test had a good positive predictive value for rectus femoris dysfunction during gait . Therefore, a positive result in the Duncan‐Ely test might be a surgical indication for RFT.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, a positive result in the Duncan‐Ely test might be a surgical indication for RFT. However, Marks et al . reported that the sensitivity of the Duncan‐Ely test ranged from 56% to 59%, and the specificity ranged from 64% to 85%.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…General visualization of the patellar movement through flexion extension may be helpful in detecting malalignment if there is a "J sign" [80,81] as result of lateral retinacular tightness or medial retinacular weakness. Decreased quadriceps flexibility, specifically rectus femoris tightness, can be assessed by using the Ely Test [82]. …”
Section: Discussionmentioning
confidence: 99%